PENGARUH KECERDASAN EMOSIONAL DAN PERILAKU BELAJAR TERHADAP PEMAHAMAN AKUNTANSI MAHASISWA UNIVERSITAS ADVENT INDONESIA (UNAI) - Riky Sai Maruli; Olivia Fransisca Moniaga (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2022)
Every student of the Accounting Study Program should understand accounting. This study aims to determine how far the students' understanding of Advent Indonesia University students regarding Accounting with Emotional Intelligence and Learning Behavior as independent variables. The population for this study was students of the Faculty of Economics and the sample was students of the accounting study program as many as 98 respondents and used convenient sampling to determine the sample. The results of this study indicate that partially there is an influence between Emotional Intelligence and Learning Behavior on Accounting Understanding. Likewise, simultaneously or simultaneously there is a significant effect of the two independent variables, namely Emotional Intelligence and Learning Behavior on Accounting Understanding.